2019
DOI: 10.3390/metabo9110252
|View full text |Cite
|
Sign up to set email alerts
|

A Lipidomic Analysis of Docosahexaenoic Acid (22:6, ω3) Mediated Attenuation of Western Diet Induced Nonalcoholic Steatohepatitis in Male Ldlr -/- Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a major public health problem worldwide. NAFLD ranges in severity from benign steatosis to nonalcoholic steatohepatitis (NASH), cirrhosis, and primary hepatocellular cancer (HCC). Obesity and type 2 diabetes mellitus (T2DM) are strongly associated with NAFLD, and the western diet (WD) is a major contributor to the onset and progression of these chronic diseases. Our aim was to use a lipidomic approach to identify potential lipid mediators of diet-induced NASH. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 88 publications
(138 reference statements)
1
41
0
Order By: Relevance
“…In comparing the REG + Air and REG + WF groups, the WF-exposed animals demonstrated a significantly higher abundance of lyso-PI (18:0) than the REG + Air group. It has been shown that increased levels of lyso-PI (18:0) in liver tissue is an indicator of hepatic inflammation [ 28 ]. The significantly higher abundance of this lipid in the livers of REG + WF exposed rats compared to all other treatments indicated the inhalation exposure to WF likely resulted in hepatic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In comparing the REG + Air and REG + WF groups, the WF-exposed animals demonstrated a significantly higher abundance of lyso-PI (18:0) than the REG + Air group. It has been shown that increased levels of lyso-PI (18:0) in liver tissue is an indicator of hepatic inflammation [ 28 ]. The significantly higher abundance of this lipid in the livers of REG + WF exposed rats compared to all other treatments indicated the inhalation exposure to WF likely resulted in hepatic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The high-performance liquid chromatography (HPLC) and mass spectrometry methods used for the analysis of plasma oxylipins was based on methods previously described for the analysis of oxylipins in liver ( 24 ). The analysis was performed using a Shimadzu Prominence HPLC system (Shimadzu, Columbia, MD) coupled to an Applied Biosystems 4000 QTRAP (AB SCIEX, Framingham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Methyl tert-butyl ether (MTBE) extraction, which has been popular recently, is undergoing various modifications and shows very good efficiency over classical methods [ 69 ]. In the study of obesity, MTBE extraction is used to isolate lipids from liver tissue [ 77 ], skeletal muscle [ 78 ], adipose tissue [ 79 ] and plasma [ 50 , 72 ].…”
Section: Methods Of Sample Preparation For Lipidomic Studiesmentioning
confidence: 99%